To solve the problem, let's analyze the relationships given:
-
If m∠1 and m∠3 are supplements, this means: \( m∠1 + m∠3 = 180^\circ \)
-
If m∠2 and m∠3 are also supplements, this means: \( m∠2 + m∠3 = 180^\circ \)
Now we have the following two equations:
- \( m∠1 + m∠3 = 180^\circ \) (Equation 1)
- \( m∠2 + m∠3 = 180^\circ \) (Equation 2)
From these two equations, we can set them equal to each other since both equal 180°:
\[ m∠1 + m∠3 = m∠2 + m∠3 \]
We can subtract \( m∠3 \) from both sides:
\[ m∠1 = m∠2 \]
This tells us that angles 1 and 2 have equal measures, which means:
\[ ∠1 ≅ ∠2 \]
Thus, the correct conclusion is:
C. \( ∠1 ≅ ∠2 \)